Aerial Oxidation of a VIV-Iminopyridine Hydroquinonate Complex: A Trap for the VIV-Semiquinonate Radical Intermediate - Stylianou, Marios; Drouza, Chryssoula; Giapintzakis, John; Athanasopoulos, Georgios I.; Keramidas, Anastasios D. (My University, 2015)
The reaction of 2,5-bis[N,N′-bis(2-pyridyl-aminomethyl)aminomethyl]-p-hydroquinone (H2bpymah) with VO2+ salts in acetonitrile or water at a low pH (2.2-3.5) results in the isolation of [{VIV(O)(Cl)}2(μ-bpymah)], the p-semiquinonate complex [{VIV(O)(Cl)}2(μ-bpymas)](OH), the cyclic mixed-valent hexanuclear compound [{VV(O)(μ-O)VIV(O)}(μ-bpymah)]3, and [(VVO2)2(μ-bpymah)]. [{VIV(O)(Cl)}2(μ-bpymas)](OH) is an intermediate of the radical-mediated oxidation of [{VIV(O)(Cl)}2(μ-bpymah)] from O2. At lower pH values (2.2), a reversible intramolecular electron transfer from the metal to the ligand of [{VIV(O)(Cl)}2(μ-bpymas)](OH) is induced with the concurrent substitution of chlorine atoms by the oxygen-bridging atoms, resulting in the formation of [{VV(O)(μ-O)VIV(O)}(μ-bpymah)]3. The metal complexes were fully characterized by X-ray crystallography, infrared (IR) spectroscopy, and magnetic measurements in the solid state, as well as by conductivity measurements, UV-vis spectroscopy, and electrochemical measurements in solution. The oxidation states of the metal ions and ligands were determined by the crystallographic data. The [{VIV(O)(Cl)}2(μ-bpymah)]-[{VIV(O)(Cl)}2(μ-bpymas)](OH) redox process is electrochemically reversible. The VIV ion in the semiquinonate compound exhibits a surprisingly low oxophilicity, resulting in the stabilization of OH- counterions at acidic pH values. An investigation of the mechanism of this reaction reveals that these complexes induce the reduction of O2 to H2O2, mimicking the activity of enzymes incorporating two redox-active centers (metal-organic) in the active site.
Keywords: Bis(2-methylpyridyl)amine; Paraformaldehyde; Sodium vanadate; NMR Spectroscopies